Electrochemical Impedance Spectroscopy Data from Solid Oxide Cells Undergoing Co-Electrolysis: The Influence of Rig Inductance. (2nd June 2015) - Thompson, Alison R; Call, Ann V; Cumming, Denis J; Sinclair, Derek C; Elder, Rachael H
Abstract : High temperature solid oxide cells (SOCs) are used for co-electrolysis of carbon dioxide and steam for the production of synthetic fuels. SOC rate-limiting processes can be investigated using Electrochemical Impedance Spectroscopy (EIS), but first, test rig contributions must be subtracted: inductance in particular. Here we illustrate the effect of inductance correction L on interpretation methods, including: impedance Z* and electric modulus M* formalisms, the Analysis of Differences in Impedance Spectra (ADIS) and the determination of Distribution of Relaxation Times (DRT). For inductances in the range 10 -7 H, results were sensitive to small changes in L, giving a significant change in high frequency Z * and M * data. This causes underestimation of the SOC polarisation resistance. ADIS results are less affected, due to the nature of the subtraction method, whereas DRT is highly sensitive to inductance, hence care must be taken to optimise inductance correction, to obtain accurate results.